EXPLORING CHALLENGES AND BARRIERS FACED BY PAKISTANI SCHOLARS AND RESEARCHERS IN PUBLISHING THEIR WORK - Azhar Ahmad; Musaddaq Ishtiaq Cheema; Dr. Perveen Akhter Farhat (International Journal of Contemporary Issues in Social Sciences, 2023)
In Pakistani context publishing work is arduous mission for scholars and researchers and they often face publication challenges and barriers. Anyhow if they complete their research work it become pain striking for them to find a suitable HEC approved journal for publication because there are many fake publishers and journals on social media. The present research is an effort not only to unveil these challenges and barriers but also to find solutions. By using qualitative research method, the researchers randomly meet 360 participants from all areas of Pakistan and by using survey technique face-to-face asked seven close-ended and two open-ended questions for the purpose of data collection. The data was collected and presented in figures and tables. The research findings revealed many challenges and barriers and researchers tried to address these hurdles through this valuable research work. The researchers also give some recommendations for scholars and researchers, and pointed out that there is need to conduct more research studies regarding publication to facilitate young scholars and researchers.